(3JCKjQ GdehGQO GdHTQjI hGdejRI GdJfGaSjI aj GdHfhc GdLRGFQjI (B:s (3Hfc GdadGMI hGdJfejI GdQjajI fehPLG (B/s - (3HGOjS, eLGfjs ((3bSfWjfI (B:s (3CdaG ddhKGFb ,s, 2017)
(3f ehVhY GdehGQO GdHTQjI hOhQgG aj aYGdjI GdfTGW GdHfcj jcJSj CgejI HGdZI NGUI aj Xd GdJMhdGJ hGdJZjQGJ GdJj JTgOgG GdSGMI GdeUQajI GdYGdejI aj Xd XghQ eG jYQa HGbJUGO GdeYQaI hGdPj CUHM CSGS GdJejR ajg jYJeO HGdOQLI GdChdi Y`di EOGQI GdehGQO GdHTQjI hJfejI GdcaGAGJ Ydi eSJhi GdHfhc HeG jVef JMbjb GdejRI GdJfGaSjI hjVef GSJOGeJgG(B. (3hdPdc LGA gPG GdcJGH djHMK aj ObGFb gPG GdehVhY hGYJeOfG ajg Ydi GdNWhGJ GdJGdjI EP LGA aj GdaUd GdChd GdeYfhf HGdEWGQ GdefgLj ddcJGH(B: (3JMOjO GdeTcdI hGdaQVjGJ hUhdG Edi GdefgL hGdOQGSGJ GdSGHbI(B. (3CeG GdaUd GdKGfj cGf YfhGfg eaGgje CSGSjI Mhd EOGQI GdehGQO GdHTQjI hbO GMJhi Ydi GdeHMK GdChd JfGhdfG ajg eGgjI hXjaI GdehGQO GdHTQjI CeG GdeHMK GdKGfj JfGhdfG ajg eGgjI EOGQI GdehGQO GdHTQjI hGdeHMK GdKGdK aJWQbfG ajg Edi EYWGA eaGgje YGeI Mhd GdcaGAGJ(B. (3hajeG jNU GdaUd GdKGdK abO LGA Ydi GdfMh GdJGdj(B: (3eSGgeI GdehGQO GdHTQjI aj JMbjb GdejRI GdJfGaSjI hJe JbSjeg Edi KdGKI eHGMK aGdeHMK GdChd YHGQI Yf eaGgje CSGSjI Mhd GdejRI GdJfGaSjI CeG GdeHMK GdKGfj abO NUU dOQGSI GdejRI GdJfGaSjI aj GdHfhc hGSJQGJjLjGJgG hGdeHMK GdKGdK cGf Mhd GdehGQO GdHTQjI ceUOQ ddejRI GdJfGaSjI(B. (3hCeG GdaUd GdQGHY cGf ejOGfjG EP ajg GdLOGhd hGdJYdjbGJ hCge GdfJGFL(B, (3haj GdCNjQ LGAJ GdNGJeI LeYfG ajgG Cge GdfJGFL hPjdfGgG HJhUjGJs
Keywords: (3GdHfhc GdLRGFQjI s; (3GdJfejI GdQjajI s; (3Hfc GdadGMI s; (3GdehGQO GdHTQjI s